Factors affecting consumers' intention towards green banking in Malaysia - Yee, Candy Jia En; Chan, Li Yi; Chung, Yen Zhi; Teng, Zi Man (2024)
As green banking is a new trend in Malaysia, some Malaysians are still unfamiliar with and unaware of the idea of green banking. Also, there are insufficient studies in Malaysia that are related to consumers’ intention towards green banking. Therefore, this study aims to examine the factors affecting consumers’ intention towards green banking in Malaysia. The factors include consumer awareness, subjective norms, perceived trust, and security and privacy. Besides, questionnaires were distributed to 384 Malaysians to collect the primary data and information to assess the respondents’ understanding of green banking. In this study, several analysis tests have been carried out using SPSS version 29.0, including descriptive analysis, reliability test, multicollinearity test, normality test, multiple linear regression analysis, and Pearson correlation. The analysis results show that perceived trust has an insignificant influence on consumers’ intention to engage in green banking in Malaysia. However, the analysis indicated that consumer awareness, subjective norms, and security and privacy have significantly affected the consumers’ intention towards green banking in Malaysia. Therefore, this study is helpful for professionals in a particular field who are willing to improve their intention towards green banking and contribute to a more in-depth and comprehensive research study